Angiographic Correlation between Coronary and Renal Artery Lesions in Patients Undergoing Simultaneous Coronary and Renal Angiography - Safiuddin, Mohammad; Habib, SM Ahsan; Uddin, Mir Jamal; Kauser, Mohammad Abu; Khan, Md Saif Ullah; Islam, Sirajul; Choudhury, Minhaj Rahim; Rahman, Fazlur; Safi, Shahnaj Binte (University Heart Journal, 2012)
Our aim was to see the association between lesions in coronary arteries and atherosclerotic renal artery stenosis (RAS) in suspected IHD patient. Data collected prospectively from 200 consecutive patients who underwent simultaneous coronary and renal angiography in suspected IHD patients. In 168 individuals of the study population, significant CAD was present (84%). Prevalence of RAS was 11% (22 patients). Significant (?50% luminal diameter stenosis) RAS was present in 12 patients (6%). Older age, higher systemic blood pressure at the time of catheterization, and 3-vessel coronary artery disease (CAD) were more associated with significant RAS. Simultaneous renal angiography is justified in patients with significant CAD particularly in older patients with hypertension. DOI: http://dx.doi.org/10.3329/uhj.v8i1.11664 University Heart Journal Vol. 8, No. 1, January 2012